The social science of Hayek's 'The sensory order' - Butos, William N. (Emerald, 2010)
"The Social Science of Hayek's The Sensory Order" systematically examines the relevance and significance of Hayek's cognitive psychology for economics and social science, and is the only publication of its kind to do so. Sixteen original papers are divided into four parts in this volume: Hayek's Cognitive Psychology, Evolution, and Social Theory; Hayek's Cognitive Psychology and Economics; Hayek's Cognitive Psychology, Institutions, and Broader Social theory; and The Place of The Sensory Order in Hayek's Oeuvre: A Mini-Symposium. Papers examine Hayek's cognitive psychology from the perspective of evolutionary theory, economics, market and social institutions, and broader social theory. Part of "The Advances in Austrian Economics Series", this book will appeal to people working in a variety of traditions in economics and related disciplines. Although Austrian school economists are the primary audience, those working in public choice, new institutionalism, complexity theory, cognitive or behavior economics, entrepreneurship, and other areas will find great value in the series. This volume is edited by William Butos, Professor of Economics, Trinity College, Hartford and Visiting Research Fellow, New York University, Austrian Economics Program.
Keywords: Hayek, Friedrich A. von -- (Friedrich August), -- 1899-1992.; Social sciences.; elektronické knihy; electronic books